The testimonial uncanny : Indigenous storytelling, knowledge, and reparative practices - Emberley, Julia, 1958- (State University of New York Press, 2014)
"Introduces readers to cultural practices and theoretical texts concerned with bringing Indigenous epistemologies to the discussion of trauma and colonial violence."--Back cover